2017
DOI: 10.3389/fphys.2017.00335
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the TRPM2 and TRPV1 Channels through Hypericum perforatum in Sciatic Nerve Injury-induced Rats Demonstrates their Key Role in Apoptosis and Mitochondrial Oxidative Stress of Sciatic Nerve and Dorsal Root Ganglion

Abstract: Sciatic nerve injury (SNI) results in neuropathic pain, which is characterized by the excessive Ca2+ entry, reactive oxygen species (ROS) and apoptosis processes although involvement of antioxidant Hypericum perforatum (HP) through TRPM2 and TRPV1 activation has not been clarified on the processes in SNI-induced rat, yet. We investigated the protective property of HP on the processes in the sciatic nerve and dorsal root ganglion neuron (DRGN) of SNI-induced rats. The rats were divided into five groups as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 57 publications
5
53
0
Order By: Relevance
“…The most probable explanation for this decrease is the lesion of the axons, which prevents the transport of AF488 and AF647 dyes from the examined areas to DRG somata. However, the apoptosis of the injured and neighboring DRG neurons following SNI-type nerve injury could be another explanation for the decrease in innervating DRG neurons [21,22]. The origin of the newly labeled DRG somata is most probably the result of the dye uptake by the axons, which sprouts from the neighboring areas and not from the regrowth of injured axons [7,11,12] (see also Figure 5, here).…”
Section: Discussionmentioning
confidence: 96%
“…The most probable explanation for this decrease is the lesion of the axons, which prevents the transport of AF488 and AF647 dyes from the examined areas to DRG somata. However, the apoptosis of the injured and neighboring DRG neurons following SNI-type nerve injury could be another explanation for the decrease in innervating DRG neurons [21,22]. The origin of the newly labeled DRG somata is most probably the result of the dye uptake by the axons, which sprouts from the neighboring areas and not from the regrowth of injured axons [7,11,12] (see also Figure 5, here).…”
Section: Discussionmentioning
confidence: 96%
“…We used commercial H. perforatum extract (HP) from Indena Inc. (Indena Industria Derivati Naturali, S.p.A. Viale Ortles, Milan, Italy) (Özdemir et al, 2016;Uslusoy et al, 2017). Contents of total hypericin, flavonoids, and hyperforin in the extract were analyzed by the company, and their rates were 0.10-0.30, 6.0, and 6.0%, respectively.…”
Section: Hypericum Perforatum Extract (Hp)mentioning
confidence: 99%
“…John's wort' Hypericum perforatum is a wellknown traditional plant, and it has been used in the treatment of several diseases such as depression, inflammatory, and skin diseases (Meinke et al, 2012;Nazıroğlu, 2016). The main components of H. perforatum are hyperforin, flavonoids, hypericin, and their anti-apoptosis and antioxidant properties through inhibition of TRPM2 channel were reported in neuropathic pain, neutrophil activation and mechanical brain injury (Nazıroğlu et al, 2014a(Nazıroğlu et al, , 2014b(Nazıroğlu et al, , 2014cUslusoy et al, 2017). In addition, involvements of HP through inhibition of TRPM2 channels in the mechanical sciatic nerve and spinal cord injuries were recently reported (Pogatzki-Zahn et al, 2005;Özdemir et al, 2016;Uslusoy et al, 2017;Uslusoy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsushita et al (2018) concluded that delivery of NA reduces the activity of transient receptor potential vanilloid type 1 (TRPV1) channels in dorsal sensory neurons. TRPV1 is a well-known nociceptionmediating ion channel and is mainly expressed in peripheral Aδ-and C-fibres as well as throughout the CNS, which overloads Ca 2+ entry through the channels involved in neuropathic pain (Chen et al, 2015;Ren et al, 2015;Uslusoy, Nazıroğlu, & Çiğ, 2017). The contribution of TRPV1 has also been evaluated in several rodent models of neuropathic pain.…”
mentioning
confidence: 99%